The Occurence of Anxiety on Heart Failure Patients in Pekanbaru - Malfasari, E (KnE Life Sciences, 2019)
Heart failure (henceforth; HF) is defined as a global pandemic. Most of HF patients feel uncomfortable with their pain or sign and symptom of cardiovascular disorder. It made patients’ feeling worry, feeling not having any hope with their disease. That feeling is anxiety and it can make HF become more serious condition. The purpose of this study was to detect prevalance of anxiety in HF patient at RSUD Arifin Achmad Riau Province. This study was a descriptive reseach analysis. DASS 21 with part of anxiety was used for anxiety measurement. It had been examided through validity and reliability test. This study used accidental sampling and had 50 respondents. The research data were taken on July 20